BERPIKIR POSITIF DAN HARGA DIRI PADA WANITA YANG MENGALAMI MASA PREMENOPAUSE - Euis Sri Damayanti; Alfi Purnamasari (Universitas Ahmad Dahlan, 2011)
The study aims to determine the relationship between positive thinkingwith self-esteem in women with premenopausal period. Subjects werepremenopausal women who ages between 40-50 years old. The studyused quantitative methods. This study used scale to get the data, namelyScale Positive Thinking and Self-Esteem Scale. The result showed asignificant coefficient correlation with r = 0.465. Positive thinking has about21.6% explaining effect on the dependent variables and 78.4% influencesby other factors. Majority participants in this study have medium level ofesteem and positive thinking. Based on the result study, it can be concludedthat there was a significant relationship between positive thinking with self-esteem in women who experienced a period of premenopausal. The higherpositive thinking conducted by participant the higher their self-esteem, andvice versa.